Menjaga Mutu Pendidikan PAUD pada Masa Pandemi Covid-19 dengan Pembelajaran Jarak Jauh (PJJ) - Dariyatun Dariyatun (Universitas Sebelas Maret, 2021)
The objective to be achieved in this paper is to describe the implementation ofPAUD distance learning during the Covid-19 pandemic. Implementation of emergencylearning in early childhood education through teaching and learning without face to face. Tosupport the successful implementation of distance learning during the Covid-19 period,teachers prepare emergency RPPM and RPPH, make introductory videos to teachers and theschool environment, whatsapp groups for sharing assignments, making video tutorials forstudent learning activities, voice notes for religious introduction, and checklist sheets for dailyhabits at home.